Analysis of the specificity of obtaining educational services and adaptation of foreign citizens - Nelli I. Taraseeva; Oksana V. Baulina (Открытое образование (Москва), 2018)
The main emphasis on the training of foreign citizens in the city of Penza is done at higher educational institutions: Penza State University of Architecture and Construction, Penza State University (PSU), Penza State Technological University (PSTU), and others. The universities are well developed in training specialists with higher education in different areas, not only production, but also scientific activities. Graduates mostly return to their homeland to apply their knowledge and skills in various branches of the national economy. At the same time, many businessmen involve foreign citizens in their work, and the desire to work with foreigners increases every year. The big problem is that all of them either do not have a profession, or they need retraining or advanced training, which leads to problems with employment and education, both on budget terms and when receiving paid educational services.In our opinion, the practice of teaching foreign citizens on the Penza land should concern not only universities, but also institutions of secondary vocational education. There is a category of foreign citizens who had little chance of graduating from high school and successfully enrolled in a Russian university for a budgetary department, would prefer to receive a qualified working profession or specialty in the institutions of secondary vocational education, which would solve a number of problems related to adaptation to another culture and mentality, and will also be the first step towards higher education.Studies have shown that most foreigners do not have any education certificates and are not qualified specialists in the industries where they work. Migrants from the countries of the East: China, Turkey, Syria, Iran, etc. in most cases have a basic general education, or another option: their diplomas do not correspond to the profession by which many foreigners work in Russia. As a result: in most cases, many people are lacking knowledge for the career growth, the creation of a small business, the development of which will attract capital to various projects and increase the investment potential of the Penza region [4]. The combination of these causal relationships led to the need to create on the basis of colleges a system of secondary vocational education for the training of foreign citizens, possibly in the form of structural divisions and groups. The organization of training, in our opinion and the experience of educational and methodological activities, can represent a parallel process for vocational training programs, supplementary education programs, which, having successfully completed a full course of training in the dual system, obtain the necessary knowledge for practical work, including not only standard methods of production, but also the latest developments in the field of science and technology. When developing these programs, foreign citizens will be able not only to adapt quickly to the conditions of work in various sectors of the economy, but also to study competently and qualitatively the quality management system (QMS).Currently, vocational education passes to new management mechanisms, while the content clearly manifests innovative approaches to the modernization of the spectrum and conditions for the implementation of educational programs in accordance with the priorities of state policy in the field of secondary vocational education.